2018
DOI: 10.1213/ane.0000000000002501
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Women’s Intention to Request a Labor Epidural Analgesia, Actually Delivering With Labor Epidural Analgesia, and Postpartum Depression at 6 Weeks: A Prospective Observational Study

Abstract: Our study results did not demonstrate a significant increase in the odds for PPD at 6 weeks among women who intended to deliver with LEA but subsequently delivered without. However, we identified a protective interaction between intended LEA use and actual use on the incidence of PPD. Our data suggest an increased risk when women do not deliver as intended, particularly when not initially intending to deliver with LEA. The relationship between unplanned LEA and PPD may be mediated by a physically difficult del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 22 publications
3
72
0
Order By: Relevance
“…Our findings complement those from Orbach-Zinger and colleagues [8], who found that unmatched intention effects with respect to use of labor analgesia are significantly associated with six-week depression risk. The current study focused on the pain experience of women planning and receiving their intended labor analgesia approach.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings complement those from Orbach-Zinger and colleagues [8], who found that unmatched intention effects with respect to use of labor analgesia are significantly associated with six-week depression risk. The current study focused on the pain experience of women planning and receiving their intended labor analgesia approach.…”
Section: Discussionsupporting
confidence: 88%
“…Moderator-mediator models can be used to investigate indirect associations between pain and depression. Characterizing these indirect associations is important, because identifying explanatory factors/conditions under which primary relationships change may clarify conflicting results in published literature on the relationship between parturitional pain, analgesia, and depression symptoms [1][2][3]8]. Moderator-mediator analyses assess how the relationship between perinatal pain and depression changes (increases or decreases) for patient subgroups ("moderation" analysis).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of association between pain intensity during labor and persistent pain and postpartum depression may therefore partly be caused by a ceiling effect. Nevertheless, the literature is inconclusive when it comes to these associations; some suggest that there is an association [10] and that better pain management during birth could prevent postpartum depression [9,11,39] whilst others do not find any preventive effects of analgesia [12,13]. The conflicting findings could be related to methodological issues as mentioned, but could also be related to differences in medical procedures in the various clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest there is an association between labor pain and postpartum depression, suggesting that managing labor pain and early postpartum pain decreases the risk for depression [8][9][10]. A recent study even suggest that effective labor pain management with epidural analgesia was associated with reduced postpartum depression symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ding Ting et al reported 4 months after delivery, there was a lower incidence rate of PPD in parturients who received epidural and paracervical blockade during vaginal delivery [16]. In contrast, another study examining PPD rates among 1326 women did not demonstrate a difference between women with intrapartum epidural and those without [17]. Besides the conflicting results in the literature, the subjects of previous studies on PPD are almost aiming at nulliparous women rather than pluripara; therefore, further study is warranted.…”
Section: Introductionmentioning
confidence: 97%